PENGARUH REWARD TERHADAP MOTIVASI BELAJAR ANAK USIA DINI KELOMPOK A DI TK AISYIYAH MINASA UPA - Nur Alim Amri; Alfia Yunita (STKIP Subang, 2022)
This study aims to determine the effect of reward on learning motivation of group A early childhood in TK Aisyiyah Minasa Upa. Essay. The type of research used in this research is quantitative research with data analysis techniques using a Likert scale. as well as using the method of giving questionnaires, interviews and documentation. The population in this study were 6 children. The results of this study indicate that giving motivation greatly I nfluences the learning process which can be seen that giving rewards in learning activities that create a pleasant atmosphere can encourage children's enthusiasm and motivation. As many as four out of six students chose a score of 4 for each question, namely yes. From this, the authors conclude that more than 50% of the population in group A TK Aisyiyah Minasa Upa has high learning motivation after being given a reward. Based on the index value above, it can be concluded that the index value is included in the medium category where the score is 55.25.